Pollution of the North Caspian Sea. (Eurasian Journal of Ecology, 2016)
Review of the environmental state the ecological situation is the northern part of the Caspian Sea and the characteristics of oil pollution and its multiplicity of sources, including getting them to all parts of the environment, scattering by large water areas, accumulation in sediments, etc. Also discussed in detail the adverse natural and anthropogenic impacts on the ecology of the sea, such as oil and gas, industrial enterprise and sea level fluctuations.
Keywords: geosystem; ecology; sea coast; oil; petrochemicals; fauna; flora; MPC; toxicants; bioressurs; hydrochemistry; deposits; shallow water; water cycle; hydrography; absorption; biocenosis; offshore; landscape; chemical compound; water area